2019
DOI: 10.1371/journal.pone.0219943
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of tissue stiffness around lesion by sound touch elastography in the diagnosis of benign and malignant breast lesions

Abstract: The purpose of our study is to assess the diagnostic performance of quantitative evaluation of tissue stiffness around lesion by Sound Touch Elastography (STE) in distinguishing between benign and malignant breast lesions. A total number of 160 breast lesions from 160 female patients were examined by STE. Resona 7 was equipped with "shell" function to measure elastic modulus values of tissue in the region of surrounding lesion quantitatively. The contours of the lesion were required to be delineated. The elast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
0
16
1
Order By: Relevance
“…Consequently, in a clinical context, these lesions require biopsy [22,25]. Recently, some studies [19,26,27] have reported that UE, which can detect differences in stiffness between normal breast tissue and NMLs, can facilitate characterization of breast NMLs [19,27] and thereby avoid 46-87.5% of benign biopsies [21]. Thus, it can offer an excellent method for diagnosing breast NMLs.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, in a clinical context, these lesions require biopsy [22,25]. Recently, some studies [19,26,27] have reported that UE, which can detect differences in stiffness between normal breast tissue and NMLs, can facilitate characterization of breast NMLs [19,27] and thereby avoid 46-87.5% of benign biopsies [21]. Thus, it can offer an excellent method for diagnosing breast NMLs.…”
Section: Discussionmentioning
confidence: 99%
“… The differentiation of cancerous lesions based on elasticity measurements. Elastic modulus (E) of benign and malignant breast lesions determined by the sound touch elastography (STE) technique [ 68 ]. …”
Section: Figurementioning
confidence: 99%
“…Indeed, breast carcinomas are characterized as being more stiff than glandular tissue [ 134 ]. This has led to new clinical technologies that show that stiffness evaluated by ultrasound-based sound touch elastography may aid breast cancer diagnosis [ 164 ] while stiffness measured by ultrasound-based shear wave elastography may provide prognostic value [ 165 , 166 ]. The effects and underlying mechanisms of stiffness on normal mammary tissue and tumors have been studied in greater detail and will be discussed further.…”
Section: Mechanical Forces and Signaling In Breast Cancermentioning
confidence: 99%
“…High average stiffness measured in vivo by shear wave elastography range is seen in human lobular (181 ± 67 kPa) and ductal tumors (139 ± 56 kPa) and stiffness increases with tumor grade (benign lesions defined as < 50 kPa, Grade 1 = 88 ± 62 kPa, Grade 2 = 143 ± 55 kPa, Grade 3 = 147 ± 58 kPa) [ 166 ]. Stiffness measured by sound touch elastography showed high average stiffness in malignant lesions (40.85 kPa) over benign lesions (19.02 kPa) [ 164 ]. Supersonic shear imaging was able to distinguish stiffness differences between fat, dense tissue, benign lesions and malignant lesions (3, 45, <80, and >100 kPa, respectively) [ 169 ].…”
Section: Mechanical Forces and Signaling In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation